LIGHTING STIMULATION AS EFFORTS TO ENHANCE PERFORMANS KAMPUNG CHICKEN WITH THE IMPLEMENTATION OF DIFFERENT WAVELENGTHS OF THE LIGHT - Mei Sulistyoningsih; Rivanna Citraning Rahayu; Eko Retno Mulyaningrum; Muhammad Anas Dzakiy (Universitas PGRI Semarang, 2013)
Lighting is an important parameter of the poultry production because of strong exogenous factor in controlling a wide variety of physiological processes and behavior. The lighting allows the birds to establish harmony and sync or equate many essential functions, including body temperature and various steps that facilitate metabolic feeding and digestion. The lighting also stimulates the secretion of some hormones patterns that control most of the growth, maturity or adulthood and reproductionThis research aims to assess the influence of light color on the body weight and carcass kampung chicken. The main independent variable is the color red, blue and white. The main dependent variable consists of body weight and percentage of carcass. The variable control is the number of rations, health management, a type of chicken, and the age of the chicken.The results show that there is no real difference in the influence of different color variations of the lighting body weights (P>0,05), and the carcass of a chicken (P>0,05).Keywords : lighting stimulation, kampung chicken, body weights, carcass